Sustainable fabric choice for regularly laundered healthcare uniforms. Issue 3 (4th March 2017) - Riley, K.; Fergusson, M.; Shen, J.
Abstract : It is well known that blended fabrics dominate the healthcare uniform market for comfort and durability performance. These fabrics present problems for end of life (EOL) management by not being easily recyclable and concerns of cross-infection lead to disposal through incineration or landfill waste. Comfort of fabrics used in healthcare uniforms is important to the wearer to enable them to carry out their duties and therefore, choice of fibre is paramount to achieve this. The use of 100% polyester has the potential to provide a sustainable alternative to polyester/cotton-blended fabrics, creating a recyclable EOL option. This paper demonstrates that fabrics using a variety of polyester yarn types show different comfort performances. The selection of appropriate polyester yarns and fabric with good comfort properties could lead to a sustainable future choice for the healthcare market.